University-level entrepreneurship education: a bibliometric review using Tree of Science - Maria Angelica Cervantes Muñoz; Carlos Devece; Marta Peris Ortiz (Multidisciplinary Journal for Education, Social and Technological Sciences)
Entrepreneurship education helps students build the skills, abilities, attitudes, and aptitudes they need to start a business. Universities play a key role in educating and transforming people. However, the academic literature in this area is fragmented. This article identifies the main areas in this field throughout its history based on a review of the literature. A scientometric study was conducted based on the results of a document search in Scopus. Using Tree of Science software, the most important documents were classified based on a network of citations. The results reveal three main perspectives: the impact of entrepreneurship education, entrepreneurship education methodologies, and new trends in entrepreneurship education. Researchers can use these results to propose ways to strengthen entrepreneurship education